Pengaruh Strategi Koping terhadap Adaptational Outcomes pada Remaja setelah Putus Cinta - Kavindhi Pradana Firmansyah; Afif Kurniawan (Buletin Riset Psikologi dan Kesehatan Mental, 2022)
The research objective is to determine the effect of coping strategies on adaptational outcomes of adolescents, The research method used is explanatory quantitative and uses purposive sampling to determine the research target, namely, late adolescents aged 17–21 years who have experienced a breakup, researchers collect data using google forms distributed through online surveys and get 117 respondents who match the research criteria. The test used is hypothesis testing using multiple regression to calculate the effect simultaneously and partial regression to test one by one the influence between variables. The results in this study showed that there is a significant influence between coping strategies on adaptational outcomes, especially problem focused coping, which has a greater influence, namely, 12.3% on adaptational outcomes while emotional focused coping has a significant but smaller influence, namely, 3%, than problem focused coping in this study.